2018
DOI: 10.1021/acscatal.8b02624
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Pyrolysis to N-Doped Graphene with High-Density Pt Single Atomic Sites as Heterogeneous Catalyst for Alkene Hydrosilylation

Abstract: Development of noble-metal single atomic site catalysts with high metal loading is highly required for many important chemical reactions but proves to be very challenging. Herein, we report a Na 2 CO 3 salt-assisted one-pot pyrolysis strategy from EDTA−Pt complex to N-doped graphene with isolated Pt single atomic sites (Pt-ISA/NG) with Pt loading up to 5.3 wt %. The X-ray absorption fine structure analysis and spherical aberration-correction electron microscopy demonstrate an atomic dispersion of single Pt spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(84 citation statements)
references
References 66 publications
3
73
1
Order By: Relevance
“…A non‐supported (homogeneous) version of Pt‐DTPZ was not tested due to poor solubility in toluene. Average TOF values calculated by dividing TON per Pt by reaction time (5.4 s −1 at 60 °C, Table , entry 6) are significantly higher than previously reported values on other Pt SSCs, Pt δ+ /TiO 2 (<0.21 s −1 at 90 °C) and Pt/graphene (0.5 s −1 at 60 °C) at the same or even higher temperature, showing the superiority of our Pt‐DPTZ system. We note that metallic Pt NP are almost catalytically inactive when supported on MgO (entry 3).…”
Section: Resultscontrasting
confidence: 70%
“…A non‐supported (homogeneous) version of Pt‐DTPZ was not tested due to poor solubility in toluene. Average TOF values calculated by dividing TON per Pt by reaction time (5.4 s −1 at 60 °C, Table , entry 6) are significantly higher than previously reported values on other Pt SSCs, Pt δ+ /TiO 2 (<0.21 s −1 at 90 °C) and Pt/graphene (0.5 s −1 at 60 °C) at the same or even higher temperature, showing the superiority of our Pt‐DPTZ system. We note that metallic Pt NP are almost catalytically inactive when supported on MgO (entry 3).…”
Section: Resultscontrasting
confidence: 70%
“…The studied hard templates include SiO 2 nanospheres, branched SiO 2 nanoaggregates, ordered mesoporous SiO 2 , and MgO . The soft templates involved Na 2 CO 3 , KCl, hydrogels, and a self‐assembled FeCl 3 layer . For instance, Wan et al reported the synthesis of atomically dispersed FeN 4 on concave‐shaped octahedral carbon cages from SiO 2 coated ZIF‐8 precursors .…”
Section: Innovative Synthesis Of Sacs On Carbon Substratesmentioning
confidence: 99%
“…in 1995, the synthetic methodology and catalytic applications of single‐atom catalysts (SACs) have attracted worldwide attention. SACs have been shown to have high atom‐utilization efficiency as well as remarkable catalytic activity and selectivity . For example, various kinds of SACs have been prepared and investigated for silane oxidation, hydrogen evolution reaction, and alkene hydrosilylation .…”
Section: Figurementioning
confidence: 99%